Low-dose rivaroxaban associated with lower incidence of all-cause mortality and bleeding complications in older patients with non-valvular atrial fibrillation. (14th October 2021) - Chiou, W R; Su, M I; Lee, Y H; Lin, P L; Liu, C W
Abstract: Background: Low-dose rivaroxaban 10mg daily was used in the J-ROCKET AF trial, and it demonstrated the safety in Asian population. It remains unclear whether low-dose rivaroxaban vs. standard dose 20mg daily is associated with efficacy, safety, and net-clinical outcomes in older Asian patients with non-valvular atrial fibrillation. Purpose: To evaluate the effects of low-dose rivaroxaban on efficacies and safeties in the old patients age more than 85 years. Methods: We retrospectively enrolled the patients from medical records between Oct 2012 and Nov 2016. We used 2x2 factorial design by age of 85 years and use of low-dose rivaroxaban. The study outcomes were one-year all-cause mortality and bleeding complications. Results: The study cohort consisted of 2, 386 patients with the mean age 76.6 years (SD 10.5), 51.8% male, CHA2DS2Vsc 4.4 (SD 1.7) and HASBLED 1.6 (SD 1.0). In the age ≥85 group (n=593), low vs. standard dose rivaroxaban had a lower incidence of all-cause mortality (5.3% vs. 10.6%, P=0.021), whereas the incidence of all-cause mortality was greater in the low dose rivaroxaban compared with the standard dose in the age <85 group (3.7% vs. 1.8%, P=0.012). No significant differences of bleeding complication rates were found between the low- and standard-dose rivaroxaban regarding age <85 or ≥85 years. After adjusting for potential confounders, low dose rivaroxaban was associated with a decreased risk of all-cause mortality in the age ≥85 group (adjusted HR: 0.400 95% CI: 0.215–0.743, P=0.004), but the significant association was not found in the age <85 group (adjusted HR: 1.101 95% CI: 0.557–2.174, P=0.782). Conclusion: Low dose rivaroxaban was associated with a decreased risk of all-cause mortality in the patients with non-valvular atrial fibrillation and age ≥85 years. Funding Acknowledgement: Type of funding sources: None.